2014 IEEE 41st International Conference on Plasma Sciences (ICOPS) Held With 2014 IEEE International Conference on High-Power P 2014
DOI: 10.1109/plasma.2014.7012321
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric resonator antenna for high power RF plasma applications

Abstract: Some of the numerous applications of the inductively coupled plasma, at both atmospheric and low pressure, include plasma manufacturing, optical and mass spectroscopy, gasification and plasma reforming, semiconductor fabrication, in-space propulsion, gas lasers, ion sources, and fusion. A coil of copper or silver-plated tubing is typically used to couple the radio-frequency power into the plasma. Although this technology has been used extensively for many decades, an RF coil suffers from limitations which nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…2. The rst group ( 7 Li, 23 Na, 24 Mg, 39 K, 85 Rb, 88 Sr, 115 In, 133 Cs, 137 Ba, and 175 Lu) is governed by elements with a low rst IE, whose sensitivity increases with higher gas ow rates due to the higher sampling efficiency. Since many analytes in this group have a low mass, a higher operating power decreases the sensitivity through increased radial diffusion and possibly space charge effects at higher temperatures.…”
Section: Inuence Of Operating Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. The rst group ( 7 Li, 23 Na, 24 Mg, 39 K, 85 Rb, 88 Sr, 115 In, 133 Cs, 137 Ba, and 175 Lu) is governed by elements with a low rst IE, whose sensitivity increases with higher gas ow rates due to the higher sampling efficiency. Since many analytes in this group have a low mass, a higher operating power decreases the sensitivity through increased radial diffusion and possibly space charge effects at higher temperatures.…”
Section: Inuence Of Operating Conditionsmentioning
confidence: 99%
“…19,20 Such microwave induced plasmas have also been described with elemental MS, [21][22][23] which however did not receive much attention. Most recently a new conguration of an inductively coupled microwave plasma source was introduced, 24 which can be operated with nitrogen as plasma gas while being capable of delivering a power of up to 1.5 kW, which compares favourably with common Ar ICPs. This novel microwave inductively coupled atmospheric pressure plasma (MICAP) has already been successfully employed as a plasma source for ICP optical emission spectrometry 25 and an initial study 26 using a prototype time-of-ight MS has revealed that with solution nebulization, the sensitivities were lower by a factor of two than those of an Ar ICP coupled to the same MS. Desolvation of the aerosol was found to enhance the sensitivity signicantly and most recently solution nebulization and laser ablation sampling were employed with an ion source coupled to a quadrupole MS (QMS), where similar gures of merit to those obtained with an Ar ICP were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Theory and design of the MICAP have been described earlier, [20][21][22][23] so only qualitative descriptions of the operating principles and waveguide will be provided here. A crosssectional view of the waveguide, resonator, and torch of the MICAP is shown in Fig.…”
Section: Micap Design and Ignitionmentioning
confidence: 99%
“…The most recent contribution to the eld of microwave plasmas in analytical chemistry is the microwave-sustained, inductively coupled, atmospheric-pressure plasma (MICAP) developed by Jevtic, Menon and Pikelja in 2016. 22 The MICAP uses a microwave-driven dielectric resonator formed by an aluminum oxide ring. Inside this ring, a standard ICP quartz torch is installed.…”
Section: Introductionmentioning
confidence: 99%